Birth Asphyxia Prevalence and Related Factors in Live Births at University Hospital, Tripoli, Libya - Sabria Slaam; Noura Elawam (AlQalam Journal of Medical and Applied Sciences, 2024)
Birth asphyxia is the cause of about one-third of newborn deaths at University Hospital's Neonatal Intensive Care Unit (NICU). On the other hand, the precise burden of birth asphyxia has not been supported by modern scientific research. The purpose of this study was to assess the prevalence of birth asphyxia and its associated variables in the NICU of University Hospital in Tripoli, Libya. A descriptive cross-sectional study including 182 mother-newborn pairs delivered at a maternity ward was carried out on the sample. From January 1, 2020, until December 30, 2022, every other mother's newborn was included. Data were gathered using a checklist and a pre-tested structured questionnaire. 28.5% of cases had asphyxia [95% CI: 26.51, 35.24%]. The final model showed that birth asphyxia was positively associated at 95% CI with fetal malpresentation (AOR = 6.96: 3.16, 15.30), rupture of fetal membranes preterm (AOR = 6.30, 95% CI: 2.45, 16.22), meconium-stained amniotic fluid (AOR = 7.15: 3.07, 16.66), and vacuum delivery (AOR = 6.21: 2.62, 14.73). The occurrence of birth asphyxia continues to be a significant public health concern. Consequently, to avoid birth asphyxia due to difficulties such as fetal mal-presentation, premature fetal membrane rupture, meconium-stained amniotic fluid, and vacuum delivery, the current emergency obstetric and newborn care efforts should be reinforced. الاختناق عند الولادة هو سبب حوالي ثلث وفيات الأطفال حديثي الولادة في وحدة العناية المركزة لحديثي الولادة بالمستشفى الجامعي. من ناحية أخرى، فإن العبء الدقيق لاختناق الولادة لم يتم دعمه من خلال البحث العلمي الحديث. كان الغرض من هذه الدراسة هو تقييم مدى انتشار الاختناق عند الولادة والمتغيرات المرتبطة به في وحدة العناية المركزة لحديثي الولادة في المستشفى الجامعي في طرابلس، ليبيا. تم إجراء دراسة وصفية مقطعية شملت 182 زوجًا من الأمهات والأطفال حديثي الولادة في جناح الولادة على العينة. من 1 يناير 2020 حتى 30 ديسمبر 2022، تم إدراج كل مولود جديد للأم الأخرى. تم جمع البيانات باستخدام قائمة مرجعية واستبيان منظم تم اختباره مسبقًا. 28.5% من الحالات كانت تعاني من الاختناق [95% فاصل الثقة: 26.51، 35.24%]. أظهر النموذج النهائي أن الاختناق عند الولادة كان مرتبطًا بشكل إيجابي عند فترة ثقة 95% مع سوء تمثيل الجنين (AOR = 6.96: 3.16، 15.30)، وتمزق أغشية الجنين قبل الأوان (AOR = 6.30، 95% CI: 2.45، 16.22)، وتمزق السلى الملطخ بالعقي. السائل (AOR = 7.15: 3.07، 16.66)، وتسليم الفراغ (AOR = 6.21: 2.62، 14.73). لا يزال حدوث الاختناق عند الولادة يشكل مصدر قلق كبير على الصحة العامة. وبالتالي، لتجنب الاختناق عند الولادة بسبب صعوبات مثل سوء ظهور الجنين، وتمزق غشاء الجنين المبكر، والسائل السلوي المصطبغ بالعقي، والولادة بالشفط، ينبغي تعزيز الجهود الحالية في مجال التوليد ورعاية الأطفال حديثي الولادة في حالات الطوارئ